Segregation of dockage and foreign materials in wheat during loading into a 10-m diameter corrugated steel bin. (September 2021) - Salarikia, Alireza; Jian, Fuji; Jayas, Digvir S.; Zhang, Qiang
Abstract: Segregation of dockage and foreign materials (DFM) is an unavoidable phenomenon in bulk grain and causes many problems. In this study, distributions of DFM, and shrunken and broken kernels (SBK) were determined during loading of wheat in a 10-m diameter flat-bottom cylindrical bin. Wheat was loaded through a vertical funnel (spout) into the bin from five drop heights (1.6, 2.5, 3.4, 4.3 and 5.2 m). Samples were collected using a sampling tube (29 cm diameter and 50 cm deep) inserted vertically at five locations (0.00, 1.25, 2.50, 3.75 and 5.00 m of horizontal distances from the center) along three radii of the bin for each drop height. The impurities from each collected sample were divided into five categories with different sizes (other grains, other particles, SBK, fine particles, and dust and fragments) by sieving analyses. Impurities larger and smaller than wheat kernels were categorized as large and small impurities, respectively. Drop height significantly influenced the radial distribution of fine particles, dust and fragments, but not the distribution of other grains and other particles. Fine particles and dust and fragments mainly accumulated in the center, while SBK accumulated mostly near the wall of the bin. Both true density and apparent test weight (bulk density) of unclean wheat and test weight of clean wheat significantly changed along the radius of bin. Apparent test weight of unclean wheat was minimum in the center and close to the wall of bin. Drop height did not influence true density and apparent test weight of clean and unclean wheat. Thousand kernel weight, dimensions, and sphericity of wheat kernels were similar at different radial locations of bin for all drop heights. This study can be used as a reference for further studies on grain handling and associated effects on grain grading system and design of aeration, drying, and insect control. . Highlights: Impurities smaller than wheat kernels were highly accumulated in the center. Impurities larger than wheat kernels were found less in the mid locations. Shrunken and broken kernels were found mostly near the wall of the bin. The test weight at the mid locations were higher than that at other locations.